In a maelstrom : the history of Russian-Jewish prose (1860-1940) - Hetényi, Zsuzsa (Central European University Press, 2008)
A concise history of Russian-Jewish literature, with special attention to the prose works. Russian-Jewish literature is discussed in four periods, showing what led to the turning points (1881-82, 1897, 1917). Hetényi demonstrates why the selected epoch (1860-1940) represents a separate strand outside both Russian and Jewish national literature. Based on the theoretical sources on the subject, the book establishes the criteria of the dual cultural affiliation. The survey of Russian-Jewish literature presents the pitfalls of assimilation and discusses different forms of anti-Semitism. After showing the oeuvre of 17 representative authors as a whole, the book analyzes a number of characteristic novels and short stories in terms of contemporary literary studies. In spite of their merits, several of the texts discussed have not been published in the last 80 years or are still available only in 19th-century journals.